Out-of-pocket medical expenses in severe CHD. (20th June 2018) - Elhoff, Justin J.; McHugh, Kimberly E.; Buckley, Jason R.; Morris, Shaine A.; Simpson, Kit N.; Scheurer, Mark A.
Abstract: Introduction: Families of children born with CHD face added stress owing to uncertainty about the magnitude of the financial burden for medical costs they will face. This study seeks to assess the family responsibility for healthcare bills during the first 12 months of life for commercially insured children undergoing surgery for severe CHD. Methods: The MarketScan ® database from Truven was used to identify commercially insured infants in 39 states from 2010 to 2012 with an ICD-9 diagnosis code for transposition of the great arteries, tetralogy of Fallot, or truncus arteriosus, as well as the corresponding procedure code for complete repair. Data extraction identified payment responsibilities of the patients' families in the form of co-payments, deductibles, and co-insurance during the 1st year of life. Results: There were 481 infants identified who met the criteria. Average family responsibility for healthcare bills during the 1st year of life was 2928, with no difference between the three groups. The range of out-of-pocket costs was 50–18, 167. Initial hospitalisation and outpatient care accounted for the majority of these responsibilities. Conclusions: Families of commercially insured children with severe CHD requiring corrective surgery face an average of 3000 in out-of-pocket costs for healthcare bills during the first 12 months of their child's life, although the amount varied considerably. This information provides a framework to alleviate some of the uncertainty surrounding healthcare financial responsibilities, and further examination of the origination of these expenditures may be useful in informing future healthcare policy discussion.